The Date Palm Dust Mite Oligonychus afrasiaticus on Date Palm: Distribution, Damage, and Control Methods – A Review Article - Mehdi, Hayat M. R.; Mehdi, Husein A.; Ali, Hazim M. (Basrah Journal Of Date Palm Research, 2025)
The date palm dust mite (Oligonychus afrasiaticus McGregor) is a major pest affecting the productivity and quality of date palm fruits in the Middle East and North Africa. This review summarizes recent research on its geographical distribution, biological and feeding behavior, cultivar susceptibility, and control strategies. The mite is widely distributed across the Afrotropical, Palearctic, and Nearctic regions, with confirmed infestations in Iraq, Saudi Arabia, Iran, and Egypt, reflecting its adaptability to diverse environments. It feeds by piercing young fruits and fronds to extract sap, particularly during the early growth stages (Kimri and Khalal), causing significant reductions in fruit quality and yield. Cultivar susceptibility varies according to morphological and chemical traits, with some cultivars exhibiting relative resistance. Effective management relies on integrated approaches. Agricultural and preventive measures—including orchard sanitation, removal of weeds and infested fruits, pruning dry fronds, improving irrigation and fertilization, selecting less susceptible cultivars, and regular monitoring—reduce infestation risks and maintain ecological balance. Biological control using entomopathogenic fungi (Metarhizium anisopliae and Beauveria bassiana), plant extracts, and essential oils has demonstrated significant mite mortality and repellent effects, with efficacy increasing at higher concentrations or repeated applications. Overall, the review highlights that sustainable, integrated pest management (IPM) strategies combining preventive practices, early monitoring, and natural or biological controls are essential for mitigating the threat of O. afrasiaticus, ensuring high-quality fruit production, and minimizing the environmental and economic impacts of chemical pesticides.